2009
DOI: 10.1590/s0103-84782009005000205
|View full text |Cite
|
Sign up to set email alerts
|

Atmosfera modificada e condições de armazenamento nas características físico-químicas de jabuticabas da cultivar 'paulista'

Abstract: O objetivo deste trabalho foi avaliar o efeito de diferentes embalagens nas características físico-químicas de jabuticabas da cultivar 'paulista', sob condições de temperatura ambiente (25°C) e refrigeração (8°C). Os frutos foram analisados no início do experimento (tempo 0) e no 2°, no 4°, no 6° e no 8° dia de armazenamento, em temperatura ambiente, e no 3°, no 6°, no 9° e no 12° dia, em câmara de refrigeração, sob diferentes condições de recobrimento (controle, filme PVC, plástico de polietileno e fécula de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
2
0
6
Order By: Relevance
“…A reduction of vitamin C content was also observed during storage, which was also affected by the storage temperature, as can be seen in Figure 3E and Appendix A - Table 1A. Similar behavior was observed by Agostini et al (2009), who evaluated jabuticaba variety 'Paulista' , and also found that the storage conditions led to a reduction of vitamin C, which was higher for the fruit stored at room temperature, probably because the refrigeration process inhibited the oxidative reactions, and delayed the physiological processes, which leads to a reduction of aroma, flavor, and texture, among other attributes.…”
Section: Resultssupporting
confidence: 79%
“…A reduction of vitamin C content was also observed during storage, which was also affected by the storage temperature, as can be seen in Figure 3E and Appendix A - Table 1A. Similar behavior was observed by Agostini et al (2009), who evaluated jabuticaba variety 'Paulista' , and also found that the storage conditions led to a reduction of vitamin C, which was higher for the fruit stored at room temperature, probably because the refrigeration process inhibited the oxidative reactions, and delayed the physiological processes, which leads to a reduction of aroma, flavor, and texture, among other attributes.…”
Section: Resultssupporting
confidence: 79%
“…The analysis on the isolated effect of the packages and the evaluation days showed that there were positive correlations of the use of the packages on the maintenance of the pH of the fruits with the storage time. Agostini et al (2009) also noticed a positive effect of the modified atmosphere favored by different packages in the maintenance of the pH values during the conservation of jabuticabas.…”
Section: Sources Of Variationmentioning
confidence: 83%
“…A redução na qualidade é associada à rápida alteração da aparência, decorrente da intensa perda de água, enrugamento da casca e perda de peso; e também à fermentação da polpa (BARROS et al, 1996). Sabará' (OLIVEIRA et al, 2003;BRUNINI et al, 2004;AGOSTINI et al, 2009;VIEITES et al, 2011).…”
Section: As Jabuticabeiras Pertencem à Famíliaunclassified